Increase in succinate dehydrogenase activity in mice brain during chronic hypoxia - Cáceda, R.; Boero, J.; Arregui, A. (Acta Andina, 2025)
Succinate dehydrogenase (SDH) activity was measured in seven brain regions of mice exposed to three weeks of hypobaric hypoxia (450 torr, 4380 meters above sea level) and compared to to normoxic sea level controls. In the hypoxic group we found an increased activity of SDH in cortex an hippocampus of 40%. These results can be explained as a compensatory mechanism for the decreased activity of other components of the respiratory chain in hypobaric hypoxia, as an strategy to mantain the normal ATP production.